Discourses of joint commissioning - Cameron, A; Brangan, E; Gabbay, J; Klein, J; Pope, C; Wye, L (Wiley, 2017)
Increasing attention has focused on the role of joint commissioning in health and social care policy and practice in England. This paper provides an empirical examination of the three discourses of joint commissioning developed from an interpretative analysis of documents by Dickinson et al. (2013; BMC Health Services Research, 13) and applied to data from our study exploring the role of knowledge in commissioning in England. Based on interviews with 92 participants undertaken between 2011 and 2013, our analysis confirms that the three discourses of prevention or empowerment or efficiency are used by professionals from across health and social care organisations to frame their experiences of joint commissioning. However, contrary to Dickinson et al., we also demonstrate that commissioners and other stakeholders combine and trade off these different discourses in unexpected ways. Moreover, at sites where the service user experience was central to the commissioning process (joint commissioning as empowerment), a greater sense of agreement about commissioning decisions appeared to have been established even when the other discourses were also in play.